2018
DOI: 10.1029/2018gl080291
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of ULF Wave‐Particle Interactions With Megaelectron Volt Electrons: The Importance of Ultrahigh‐Resolution Energy Channels

Abstract: Electron flux measurements are an important diagnostic for interactions between ultralow-frequency (ULF) waves and relativistic (∼1 MeV) electrons. Since measurements are collected by particle detectors with finite energy channel width, they are affected by a phase mixing process that can obscure these interactions. We demonstrate that ultrahigh-resolution electron measurements from the Magnetic Electron Ion Spectrometer on the Van Allen Probes mission-obtained using a data product that improves the energy res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…While such a signature should be observable in existing openly available electron flux data sets from the Van Allan Probes mission, comparing the leftand right-hand columns of Figure 7 makes clear the potential benefits of higher-resolution electron flux observations. Such ultrahigh-resolution observations from the magEIS and REPT instruments onboard the RBSP satellites have recently been reported in Hartinger et al (2018) and have revealed complex structures in the modulated electron flux following a southward-Kivelson type drift-resonance signature. Arguably, some features of these structures bare a resemblance to those shown in Figure 7g; however, these were taken during an event in which drift resonance with a toroidal mode Pc5 wave occurred, for which the ULF wave profile with L-shell is distinctly different than the poloidal mode.…”
Section: General Discussion and Summarymentioning
confidence: 81%
See 1 more Smart Citation
“…While such a signature should be observable in existing openly available electron flux data sets from the Van Allan Probes mission, comparing the leftand right-hand columns of Figure 7 makes clear the potential benefits of higher-resolution electron flux observations. Such ultrahigh-resolution observations from the magEIS and REPT instruments onboard the RBSP satellites have recently been reported in Hartinger et al (2018) and have revealed complex structures in the modulated electron flux following a southward-Kivelson type drift-resonance signature. Arguably, some features of these structures bare a resemblance to those shown in Figure 7g; however, these were taken during an event in which drift resonance with a toroidal mode Pc5 wave occurred, for which the ULF wave profile with L-shell is distinctly different than the poloidal mode.…”
Section: General Discussion and Summarymentioning
confidence: 81%
“…This gives rise to a specific signature in satellite observations characterized by modulations in particle flux at the wave frequency, with a 180 • phase shift across the resonant energy (for which the unperturbed drift speed matches the azimuthal phase speed of the wave; Southwood & Kivelson, 1981). In cases of both electrons and ions, such signatures have been found in a number of event studies Dai et al, 2013;Hao et al, 2017;Hartinger et al, 2018;Mann et al, 2013;Zong et al, 2009Zong et al, , 2012. Further refinements to the theory and modeling incorporate the effects of day/night asymmetry, azimuthal localization and spectral bandwidth of the wave amplitude, and nonlinear effects on particle dynamics Degeling et al, 2007Degeling et al, , 2011Li et al, 2017Li et al, , 2018Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 88%
“…In the following we explore similar flux oscillation amplitudes as observed through a novel MagEIS data product: ultrahigh energy resolution electron measurements. Claudepierre et al (2017) and Hartinger et al (2018) have recently demonstrated a technique to obtain ultrahigh energy resolution electron measurements, which are derived from the histogram data used for background removal of the main rate channels. It is a nonstandard data product that is possible due to the designed functionality of the MagEIS instruments.…”
Section: High-resolution Mageis Datamentioning
confidence: 99%
“…The technique is based on the fact that, whereas the standard MagEIS energy channels are obtained from the full pulse-height spectrum from each MagEIS detector or pixel over a narrow pulse-height range centered on the pixel response (see Claudepierre et al, 2017), a subsampling of the full pulse-height spectrum is also retained, via onboard look-up tables, to produce the MagEIS histogram data product; these data can be used to obtain ultrahigh energy resolution fluxes when count rates are large enough. In the study of Hartinger et al (2018), these ultra-high-resolution measurements have revealed a range of complex dynamics that cannot be resolved by standard measurements. Furthermore, as Hartinger et al (2018) demonstrated using the histogram channels, the flux modulation amplitudes as observed using the standard-resolution MagEIS energy channels appear lower than the ultrahigh resolution channels, and can differ by as much as a factor of 2.…”
Section: High-resolution Mageis Datamentioning
confidence: 99%
See 1 more Smart Citation